Combination Therapy with Pyridoxine and Arginine Supplementations along with a Lysine-Restricted Diet in Individuals with Pyridoxine-Dependent Epilepsy: A Comprehensive Systematic Review - Ali Jafari; Mohammad Mehdi Abbasi; Hamid Abbasi; Sama Rahnemayan; Farnush Bakhshimoghaddam; Saeid Doaei (Current Developments in Nutrition)
Background: Pyridoxine-dependent epilepsy (PDE) is identified as a rare neurometabolic disease marked by biallelic pathogenic mutations of the ALDH7A1 gene. A combination therapy involving pyridoxine, arginine supplementation (AS), and a lysine-restricted diet (LRD) was frequently reported to effectively improve PDE through reducing neurotoxic lysine metabolites, improving seizure management, and enhancing neurodevelopmental outcomes. Objectives: The study sought to investigate the effects of mono-(pyridoxine), dual- (pyridoxine combined with AS or LRD), and triple-therapy approaches in individuals diagnosed with PDE. Methods: An extensive search was carried out across international databases, comprising Scopus, Embase, Web of Science, PubMed, and Google Scholar, to find relevant publications published before 12 November, 2024. The methodological quality assessment of chosen articles was evaluated utilizing the Newcastle-Ottawa Scale and the Joanna Briggs Institute tool. Results: Among 2097 studies reviewed, 38 met inclusion criteria, covering treatment methods for individuals with PDE including monotherapy (22 articles), dual therapy (9 articles), and triple therapy (7 articles). The results indicated that pyridoxine monotherapy is a highly effective first-line treatment in PDE that improves seizure control with minimal cognitive decline. Combining pyridoxine with an LRD or AS targets metabolic issues, reducing neurotoxic metabolites and enhancing cognitive and motor functions. Early triple therapy, within the first 6 months of life, exhibited significant benefits for seizure management and cognitive performance in patients with PDE. Conclusions: In summary, administration of pyridoxine is highly effective, particularly when combined with AS and an LRD. Triple therapy illustrates promise for improved seizure control and cognitive function, especially when initiated early. Further research is warranted.